Crafting a Foundation for Evaluating a Worksite Wellness Program - Teresa A. Hubley; Kay Dutram (Journal of MultiDisciplinary Evaluation)
Background: Businesses have been exposed to many positive accounts of the benefits of employee wellness to improve employee performance as well as reduce health and injury claims costs for the employer. However, many do not have the tools or experience to effectively demonstrate the benefits of a workplace wellness program for their own management and other stakeholders.